(untitled) (Journal of Science and Technology, 2016)
Against the background of the perennial management challenges facing the Ghanaian House Building Industry, project management practices in the implementation of Mass House Building Projects (MHBPs) is presented with a view to reflecting on their strength and weaknesses. The role of project managers (PMs) and their performance on these projects are reviewed including how they have helped or met project objectives especially in terms of completion dates and cost. The evidence gathered suggests that, professional project management services, emanating from project inception to completion can potentially help in minimizing the effects of some of the key managerial challenges. It is suggested that, all other things being equal, some characteristics of the professional project management services could be adopted and embodied into a framework within which current management practices can be advanced for improving effective delivery of future housing projects.